Alkaline oxidative cracking for effective depolymerization of biorefining lignin to mono-aromatic compounds and organic acids with molecular oxygen. (January 2018) - Lyu, Gaojin; Yoo, Chang Geun; Pan, Xuejun
Abstract: Alkaline oxidative cracking with molecular oxygen was demonstrated as an effective method to depolymerize lignin under moderate conditions. Ammonia-extracted lignin from corn stover was depolymerized to aromatics and organic acids by the alkaline oxidation. The identified products by GC-MS, NMR, and HPLC included mono-aromatic compounds (such as vanillin, p -coumaric acid, vanillic acid, acetovanillone etc.) and organic acids (such as oxalic, acetic, formic acids, etc.). The overall mass yield of quantified aromatics and organic acids varied from 24% to 58% under the investigated conditions. It was found that the yields and compositions of the products were determined by the reaction conditions (temperature, reaction time, and oxygen pressure). More vanillin and organic acids were produced with oxygen under high temperature and long time, while p -coumaric acid was the primary product under oxygen deficient condition. Graphical abstract: Alkali oxidative cracking with oxygen was investigated for lignin depolymerization. Ammonia-extracted lignin from corn stover was depolymerized into mono-aromatics and organic acids at moderate reaction conditions. Highlights: Alkaline oxidation with oxygen is an effective lignin depolymerization method. Up to 58% of lignin was converted to mono-aromatics and organic acids. Vanillin and p -coumaric acid were the major aromatics from corn stover lignin. Conditions greatly affected product composition of lignin alkaline oxidation.